2022
DOI: 10.3389/fnagi.2022.967231
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles: A new paradigm in understanding, diagnosing and treating neurodegenerative disease

Abstract: Neurodegenerative disorders (NDs) are becoming one of the leading causes of disability and death across the globe due to lack of timely preventions and treatments. Concurrently, intensive research efforts are being carried out to understand the etiology of these age-dependent disorders. Extracellular vesicles (EVs)—biological nanoparticles released by cells—are gaining tremendous attention in understanding their role in pathogenesis and progression of NDs. EVs have been found to transmit pathogenic proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 171 publications
0
4
0
Order By: Relevance
“…Two independent researchers (HBT and SSA) screened all the titles, abstracts, and full manuscripts to select articles that met the eligibility criteria. By hand, we reviewed the reference lists of eligible studies, searched Google scholar for articles measuring α‐syn in CNS‐originating EVs and detailed reviews of the literature for inclusion of eligible studies 29‐35 . Any discrepancies in article selection were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent researchers (HBT and SSA) screened all the titles, abstracts, and full manuscripts to select articles that met the eligibility criteria. By hand, we reviewed the reference lists of eligible studies, searched Google scholar for articles measuring α‐syn in CNS‐originating EVs and detailed reviews of the literature for inclusion of eligible studies 29‐35 . Any discrepancies in article selection were resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
“…By hand, we reviewed the reference lists of eligible studies, searched Google scholar for articles measuring α-syn in CNSoriginating EVs and detailed reviews of the literature for inclusion of eligible studies. [29][30][31][32][33][34][35] Any discrepancies in article selection were resolved through discussion. The complete search strategy can be found in Table S1.…”
Section: Datasourcesandsearchstrategymentioning
confidence: 99%
“…Two independent researchers (HBT and SSA) screened all the titles, abstracts, and full manuscripts to select articles that met the eligibility criteria. By hand, we reviewed the reference lists of eligible studies, screened Google scholar and detailed reviews of the literature for inclusion of eligible studies (9,13,17,20,31,51,52,54). Any discrepancies in article selection were resolved through discussion.…”
Section: Data Sources and Search Strategymentioning
confidence: 99%
“…The conventional wisdom is that a better understanding of the myriad roles of extracellular vesicles (EVs) in CNS homeostasis is essential for developing novel therapeutics to alleviate and reverse the neurological disturbances of aging [ 1 , 2 , 3 ]. Thus far, an increasing number of studies have revealed the complexities of EV-mediated cell–cell communications in the brain, predominantly emphasizing the role of EV released by brain cells under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%